Castle of refuge [large type] - Dickerson, Melanie (Thorndike Press Large Print Christian Romance, 2024)
In medieval England, nineteen-year-old Audrey, the daughter of English nobility and facially scarred by her abusive, mentally ill sister, seeks God's protection when she runs away from an arranged marriage proposal, to find true love, safety, and a purpose to her life.